A Cost-Efficient Hybrid UHF RFID and Odometry-Based Mobile Robot Self-Localization Technique With Centimeter Precision - Kammel, Christoph; Kögel, Tobias; Gareis, Matthias; Vossiek, Martin (IEEE Journal of Radio Frequency Identification, 2022)
This paper presents an indoor localization approach that determines the absolute position of a mobile robot platform with centimeter precision by fusing RFID localization results based on cost-effective, standard passive UHF RFID technology with the robot’s odometry data. The mobile robot platform is equipped with a multistatic UHF RFID interrogation system, and several RFID tags are arbitrarily placed within the localization environment, serving as landmarks. The RFID localization concept is based on phase evaluations. To overcome the problem of ambiguous position estimations due to the 2π-phase ambiguity of the RFID signal phase and mitigate the linearization problem of the nonlinear system, a novel algorithm based on an iterative multihypothesis Kalman filter is introduced. A realistic simulation setup is developed to validate the proposed filter algorithm. By tracking a UHF RFID-equipped mobile robot platform in a real-world office environment, the proposed approach is also practically tested in terms of real-time capability, everyday suitability, and multipath resistance. Given that centimeter precision is only achieved in environments with weak multipath propagation, the RFID localization results are fused with odometry data provided by the robot. This effectively compensates for offset and drift in the odometry sensor, achieving a root-mean-square localization error of 2.7 cm.<br
Keywords: autonomous robot; global localization; indoor positioning; Industry 4.0; Internet of Things; iterative unscented Kalman filter; MIMO; multihypothesis Kalman filtering; phase-based localization; radio frequency identification; RFID robot; self-localization; synthetic aperture; UHF RFID

A MIMO UHF-RFID SAR 3D Locating System for Autonomous Inventory Robots - Gareis, Matthias; Carlowitz, Christian; Vossiek, Martin (2020 IEEE MTT-S International Conference on Microwaves for Intelligent Mobility, ICMIM 2020, 2020)
As ultrahigh frequency (UHF) radio-frequency identification (RFID) is a cost-efficient, reliable technology, its use for Internet of Things applications is very attractive. The goal of three-dimensional (3D) product maps for smart warehouses is very challenging, but can be achieved with UHF-RFID. Therefore, we equipped a mobile robot platform with a commercial RFID reader and added a switching matrix to integrate a multiple input - multiple output (MIMO) synthetic aperture radar based localization concept (SARFID) with the use of eight antennas. The mobile robot platform and the MIMO localization technique together demonstrate good tag localization results. We evaluate both single-dimensional and two-dimensional synthetic aperture radar (SAR) trajectories. Their shapes are the main contributor to the achievable accuracy. The robot position is acquired by the robot's odometry data. Despite the substantial error in the robot position, we generate 3D product maps with tags labeled on objects and achieve a 3D root mean square error (RMSE) of 3.8 cm.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 3D localization; 3D product map; MIMO; SAR; SARFID; UHF-RFID

High-Accuracy 3D SAW RFID Tag Localization Using a Multi-Antenna Mobile Robot Based Synthetic Aperture Approach - Caldero, Pau; Gareis, Matthias; Vossiek, Martin (2020 50th European Microwave Conference, EuMC 2020, 2021)
Asset localization for inventory and management applications can benefit from the characteristics of surface acoustic wave (SAW) radio frequency identification (RFID), adding valuable information in Industrial Internet of Things (IIoT) ecosystems. An innovative approach using this technology combined with a multi-channel interrogation hardware integrated on a mobile robot platform under indoor conditions is studied in this work. With this novel system advance, SAW RFID tags can be localized in three dimensions within centimeter accuracy. The system concept and algorithms are described in detail in this paper. Furthermore, the performance in terms of localization accuracy is evaluated theoretically and experimentally and a root mean square error of 1.6 cm is achieved.
CRIS-Team Scopus Importer:2021-03-05
Keywords: 3D localization; RFID; SAR; SAW

Novel UHF-RFID Listener Hardware Architecture and System Concept for a Mobile Robot Based MIMO SAR RFID Localization - Gareis, Matthias; Hehn, Markus; Stief, Patrick; Körner, Georg; Birkenhauer, Christoph; Trabert, Johannes; Mehner, Tom; Vossiek, Martin; Carlowitz, Christian (IEEE Access, 2020)
In this paper, we introduce an ultra-high frequency radio frequency identification (UHF-RFID) mobile robot platform that is capable of performing fully autonomous inventory taking and stocktaking by providing three-dimensional (3D) product maps and thus making possible the concept of a smart warehouse. The proposed novel hardware architecture consists of an eight-channel UHF-RFID-listener for parallel signal phase recovery, including two different carrier leakage suppression circuits and a correlation decoder for each channel for the tag signal, which can handle a backscatter link frequency (BLF) deviation of up to 22 % to decode the tag data. The system also uses eight parallel channels for multiple-input multiple-output (MIMO) localization. For the system evaluation we labeled clothes stored in a warehouse with tags and generated their product map. The proposed localization algorithm is based on a synthetic aperture radar (SAR) MIMO approach that needs exact knowledge of the antenna positions and, therefore, of the driven trajectory. This position is provided by the robot, which takes advantage of a simultaneous localization and mapping (SLAM) algorithm, determining the position with 1 cm accuracy while generating two-dimensional (2D) maps of the surroundings. We placed ten tags at known positions to assess the system’s performance and were able to locate these tags within a root mean square error (RMSE) of 1.45 cm in 3

Particle Filter-Based SAR Approach and Trajectory Optimization for Real-Time 3D UHF-RFID Tag Localization - Gareis, Matthias; Fenske, Patrick; Carlowitz, Christian; Vossiek, Martin (2020 IEEE International Conference on RFID (RFID), 2020)
The availability of three-dimensional (3D) product maps is among the most important factors for smart warehouse environments connected to the Internet of Things. Therefore, online access to the data is a key feature that can only be provided by real-time localization systems. With the well-known synthetic aperture radar technique in combination with ultrahigh frequency (UHF) radio-frequency identification (RFID) tags, good localization results have been achieved, by labeling tags on objects and measuring the tag responses on generated trajectories, for example in warehouses, with a mobile robot platform equipped with a UHF-RFID reader. The location estimation of the tags is thus made offline after the whole synthetic aperture radar (SAR) trajectory was driven and all data are available, which can’t provide online availability of the object positions. We introduce a particle filter-based real-time localization estimation technique that involves estimating tag positions during the recording of the incoming tag signals. We first evaluate the impact of trajectories according to lateral and radial resolution and show the capability of real-time signal processing on tag counts and the amount of tag reads. We then compare our novel localization technique to the well-known grid-based approach in terms of accuracy and computational load and show the localization error improvement of our technique over the filter iteration steps by generating a 3D product map of objects labeled with standard UHF-RFID tags. The 3D root mean square error (RMSE) achieved is 2.86 cm and the computation time is reduced by a factor of more than 5

Radar Target Simulator Based on Instantaneous Intra-Chirp FMCW Parameter Estimation - Birkenhauer, Christoph; Körner, Georg; Stief, Patrick; Gareis, Matthias; Carlowitz, Christian; Vossiek, Martin; Birkenhauer, Christoph; Kuhnlein, Matthias; Korner, Georg; Stief, Patrick; Gareis, Matthias; Carlowitz, Christian; et al. (20th European Radar Conference, EuRAD 2023, 2023)
Keywords: radar target simulation; automotive radar; parameter estimation; FMCW

SAW RFID Tag Spatial Division Multiple Access Based on 3D Reflector Response Localization Using a Wideband Holographic Approach - Caldero Bardaji, Pau; Gareis, Matthias; Vossiek, Martin (IEEE Journal of Microwaves, 2022)
Surface acoustic wave (SAW) radio-frequency identification (RFID) has high potential for industrial applications, where automated identification and localization of assets represent the backbone of process controlling and logistics. However, in situations where multiple tags are simultaneously interrogated, the response patterns corresponding to the hard-coded reflectors are prone to overlap, preventing their association with the corresponding tags and, hence, the correct tag decoding. Identification and localization of multiple SAW RFID tags are addressed in this work under this challenging effect, known as collision, with a multi-antenna mobile robot-based synthetic aperture approach. Using the estimation of the spatial probability density functions of the SAW tag reflectors over a given interrogation aperture, the received impulse responses can be resolved in three dimensions and clustered with respect to their estimated locations. The performance of the proposed approach to associate and localize the signals from multiple tags was evaluated theoretically and experimentally.<br
Keywords: 3D localization; anti-collision; RFID; SAW; SDMA

Stocktaking Robots, Automatic Inventory, and 3D Product Maps: The Smart Warehouse Enabled by UHF-RFID Synthetic Aperture Localization Techniques - Gareis, Matthias; Parr, Andreas; Trabert, Johannes; Mehner, Tom; Vossiek, Martin; Carlowitz, Christian (IEEE Microwave Magazine, 2021)
In our age of global networks and the Internet of Things, communication and identification with a transponder tagged on goods and products have become increasingly important [1]. There is not only a need for the identification of the labeled objects but also for finding their exact positions in 3D space. Radio-frequency identification (RFID) offers both and is, in fact, already used in a vast field of applications, such as access control, goods logistics, indoor localization, automation, stocktaking, and many others [2]-[6]. Figure 1 illustrates a mobile robot platform for automatic inventory rounds that is used to acquire 3D product maps with ultrahigh-frequency (UHF)-RFID technolog
CRIS-Team Scopus Importer:2021-03-05